Making Biocarno Fertilizer from Marine Organic Waste to Increase the Income of the Abadi Fisherman Farmer Group in Kuala Indah Village - Hidayat, Benny; Sibayang, Nur Ulina; Jamilah (Talenta Publisher, 2024)
Management of marine organic waste can also be used as a solution to reduce marine waste and prevent global warming considering that the sea has many roles in supporting the life of living creatures and maintaining the ecosystem. The organic fertilizer that will be produced will be called